Predıctıon Of Mandıbular Growth Rotatıon - Haluk İşeri; Ayşegül Köklü (Galenos Yayinevi, 1989)
Growth of the facial skeleton and prediction of the mandibular rotation has been subjected to a great number of studies in recent years. For prediction of the mandibular growth rotation, mandibular plane inclination in relation to the cranial base has been used frequently for many years. On the other hand, besides individual variability, statistical studies have also implied that the mandibular inclination in relation to the cranial base can be considered as a morphogenetic feature, which reflects the actual growth rotation pattern of the mandible only to a moderate degree. Thus, for a better prediction of mandibular growth rotation, some other features have to be used together with the mandibular plane inclination.